Modelling of Road Embankment on Soft Soil with Geogrid as Soil Reinforcement - Zawil, Muhammad Nurul Fairuz Bin Zawil Anuar; Nur Faezah Yahya (Progress in Engineering Application and Technology, 2021)
As the population of people in this country increasing, the number of road user also increasing. The road network plays a major role in the development of the country. Often these roads are constructed on weak structure of soil such as soft soil. Hence, this paper use geogrid as the soil improvement.  The purpose of this paper is to determine the maximum value of settlement at different location of geogrid with different type of geogrid in the road embankment. Next, to compare the maximum value of settlement with different type of geogrid. Lastly, to determine the type of material with minimum value of settlement. This research use 2D plaxis software to analyze the settlement of soil. As conclusion, the lowest location of geogrid is the best location and the geogrid that is made from polypropylene is the best material and the strongest to withstand the load and minimize the settlement.